A Self-existence of the #TBSBabes Community Member through The Refill Station program - Azalia, Annisa Pramesti; Al Husain, A. Hasan; Seprina, Waode (Mediator: Jurnal Komunikasi, 2024)
The beauty industry is considered the most significant contributor to plastic waste in Indonesia and companies within this industry are expected to prioritize environmental concerns. Since 2022, beauty industries in Indonesia have shifted their trends towards using more natural and eco-friendly products. This research aims to analyze the self-identity of members of the #TBSBabes Community through The Body Shop's Refill Station program. The study is conducted using a qualitative method with a phenomenological approach to analyze and describe the data. Applying Alfred Schutz's phenomenological theory, two types of motives were identified among members of the #TBSBabes Community: habitual motives and environmental motives. Additionally, there are educational motives related to environmental preservation. Based on these motives, researchers interpret the form of self-identity shaped by the participation of #TBSBabes Community members in the Refill Station program as being recognized by their social environment as eco-beauty content creators. Each human behavior carries meaning, as demonstrated in this research by members of the #TBSBabes Community seeking recognition in their social environment.